1988
DOI: 10.1295/polymj.20.399
|View full text |Cite
|
Sign up to set email alerts
|

ESCA Analysis of Polymer–Acceptor Interactions in Chemically Synthesized Polypyrrole–Halogen Complexes

Abstract: ABSTRACT:X-Ray photoelectron spectroscopy (XPS) studied have been performed on conductive polypyrrole (PPY)-halogen complexes, such as PPY-I2, PPY-Br2, and PPY-Cl2 complexes, prepared by the simultaneous chemical polymerization and oxidation of pyrrole by the respective halogens. Substantial halogenation of the pyrrole ring was observed in the case of PPY -Cl2 and PPY-Br 2 complexes. In the case of PPY -Br 2 complex, the ratio of covalent to ionic bromide content can be effectively varied over a wide range by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 18 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…The binding energy at 618.8 eV is associated with I 3d 5/2 XPS spectrum which is attributed to I 3 -anions in I 2 -PANI/TiO 2 thin film. 27,40,41 It is noteworthy that the I 2 dopant is attached interstitially with PANI in the form I 3 -anions by PECVD. Thus, it again affirms the doping of I 2 in I 2 -PANI/TiO 2 thin film by the sophisticated PECVD technique.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy at 618.8 eV is associated with I 3d 5/2 XPS spectrum which is attributed to I 3 -anions in I 2 -PANI/TiO 2 thin film. 27,40,41 It is noteworthy that the I 2 dopant is attached interstitially with PANI in the form I 3 -anions by PECVD. Thus, it again affirms the doping of I 2 in I 2 -PANI/TiO 2 thin film by the sophisticated PECVD technique.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation level and the corresponding doping level, calculated from the peaks area ratios of Cl 2p existing in the PPy matrix to N 1s in XPS spectra with individual correction using the appropriate instrument sensitivity factor [45,48,[53][54][55], are shown in Table 3. Inspecting the relationship between conductivities and N þ /N ratios of samples 1c, 2c and 5c, it is found that this relationship is consistent with the general concept of a higher N þ /N ratio being responsible for a higher conductivity [45,48,[53][54][55]. However, contrary results are also found on over-oxidized and aged PPy films.…”
Section: Clo à 4 -Doped Ppy Films Prepared In Aqueous Solutions (Sampmentioning
confidence: 99%
“…However, the small peak at about 288.5 eV is as yet unidentified, but the high binding energy suggests the presence of electron-withdraw atoms, possibly as a result of surface oxidation. 8 Finally, at 291.0eV, a shake-up satellite arising from the aromaticity of the polymer and acceptor can be resolved.…”
Section: Resultsmentioning
confidence: 98%
“…Similar line shape has been observed in other oxidized PPY s prepared electrochemically 6 or chemically. 8 The peak widths (FWHM) for the main component are 2.0eV and 1.8eV, respectively, for the PPY-DDQ and PPY-chloranil complex. The broader peak observed in the former is probably due to the contribution from the cyano group of DDQ.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation